1992
DOI: 10.2135/cropsci1992.0011183x003200010013x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Selection on Winter Barley Composite Cross XXVI Affects Winter Survival and Associated Traits

Abstract: Winterhardiness of winter barley (Hordeum vulgare L.) has not been improved greatly during the last 40 yr. Explanations range from a presumed lack of genetic variance for hardiness to a lack of effective selection in winter barley improvement programs. Previous research in Montana utilized recurrent selection in composite crosses containing male sterility to increase genetic recombination and improve winterhardiness. Composite Cross XXVI (CCXXVI) was subjected to winter selection pressure at various Montana lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Results from experiments investigating the effect of natural selection on the winter survival of barley CCPs indicate that natural selection did increase winter survival although not uniformly over different generations [48]. In bulk populations of winter oats an improvement in winter hardiness could only be found in populations with low initial survival levels [49,50].…”
Section: Yield and Yield Componentsmentioning
confidence: 96%
See 1 more Smart Citation
“…Results from experiments investigating the effect of natural selection on the winter survival of barley CCPs indicate that natural selection did increase winter survival although not uniformly over different generations [48]. In bulk populations of winter oats an improvement in winter hardiness could only be found in populations with low initial survival levels [49,50].…”
Section: Yield and Yield Componentsmentioning
confidence: 96%
“…In bulk populations of winter oats an improvement in winter hardiness could only be found in populations with low initial survival levels [49,50]. Also, apparent advances made in winter survival in one year can reverse in later generations due to a lack of competitive ability of the hardy types later in the growing season [49], when non-hardy types that were not eliminated resurface and restore themselves as major components in the population [48]. This shows that complex traits such as winter hardiness, that were not a main focus when establishing CCPs, are hard to achieve through natural selection only.…”
Section: Yield and Yield Componentsmentioning
confidence: 99%
“…One relatively easy way to test this would be to study the plant height of an evolving population over several generations. In an early study on barley populations, Allard & Jain [26] found no increase in plant height over the course of fifteen successive generations, while other studies on barley populations suggested that natural selection favoured taller plants [31,36].…”
Section: Limitations Of Evolving Populationsmentioning
confidence: 97%
“…For barley, the CC approach has been shown to be extremely powerful: innumerable elite varieties released in the twentieth century trace their origin to the CC populations produced in California in the 1920s while the CC populations have remained genetically variable even after 50 generations of propagation at single sites (Allard 1988). When exposed to new environments including diseases that had not been important in the original environment, the CC populations proved to be readily adaptable to these (e.g., Danquah and Barrett 2002a, b;Hensleigh et al 1992;Webster et al 1986). Similarly, French work on dynamic management of wheat CCs shows that adaptive changes within the populations in response to local selection pressures occur, while simultaneously maintaining genetic variation and thus adaptability (Goldringer et al 2006).…”
Section: Genetic Resources For Mixed Croppingmentioning
confidence: 99%